METODE CONTROL CHART DAN FISHBONE TERHADAP PRODUK POWER HOUSE PADA UNIT PENGOLAHAN SAMPAH TERPADU LINGKUNGAN HIDUP PROVINSI DKI JAKARTA - Huzair Tarmizi; Siwi Nur Indriyani (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
This Study aims to control the quality of power house production found in the Bantar Gebang Integrated Waste Management Unit (UPST). The Problem Faced is that there is still damage to the intercooler due to water entering the pipeline, so there is damage to the engine so that methane can not be produced into electricity. The method used is a statistical method and a quality control tool that is seven tools. The statiscal tools used in this study are : control charts and cause and effect diagram (fish bone).